2012
DOI: 10.1089/vim.2012.0033
|View full text |Cite
|
Sign up to set email alerts
|

A Toll-Like Receptor 3 Ligand Enhances Protective Effects of Vaccination Against Marek's Disease Virus and Hinders Tumor Development in Chickens

Abstract: Marek's disease (MD) is caused by Marek's disease virus (MDV). Various vaccines including herpesvirus of turkeys (HVT) have been used to control this disease. However, HVT is not able to completely protect against very virulent strains of MDV. The objective of this study was to determine whether a vaccination protocol consisting of HVT and a Toll-like receptor (TLR) ligand could enhance protective efficacy of vaccination against MD. Hence, chickens were immunized with HVT and subsequently treated with syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Contrary to our findings the expression of IL-1β was significantly increased in spleen of chicken embryos by treatment of CpG ODN (Dar et al, 2009). This difference may be due to type of cells present in CAM (Parvizi et al, 2012). The expression of IL-1β in CAM may recruit other cells like macrophages to the site of virus replication and these cells may be the source of iNOS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings the expression of IL-1β was significantly increased in spleen of chicken embryos by treatment of CpG ODN (Dar et al, 2009). This difference may be due to type of cells present in CAM (Parvizi et al, 2012). The expression of IL-1β in CAM may recruit other cells like macrophages to the site of virus replication and these cells may be the source of iNOS.…”
Section: Discussioncontrasting
confidence: 99%
“…Although, CpG ODN significantly increased the expression of OAS in spleen of chicken embryos (Dar et al, 2009) and lung & spleen of chicken . This difference may be due to the type of cells present in the CAM (Parvizi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ligands for TLRs are used as adjuvants that stimulate immune responses, leading to protection against infectious diseases. We have demonstrated that the administration of TLR3 [133], TLR4 and TLR21 ligands [134] reduces the incidence of tumours and MDV genome copy numbers in the infected birds. The importance of TLR in providing protection against tumour development could be extrapolated from the results demonstrating significantly higher basal expression levels of TLR3 and TLR7 in uninfected chicken cells isolated from resistant chicken lines compared to the susceptible lines [135].…”
Section: Persistence In the Face Of Vaccinationmentioning
confidence: 99%
“…The TLR3 ligand poly(I:C) administered as an adjuvant concomitantly with herpesvirus of turkeys (HVT) vaccine in chickens could enhance the protective efficacy against Marek’s disease tumors [40]. A recent study has shown that poly(I:C) has the ability to enhance host immunity against avian influenza viruses (AIV) H4N6 including a significant decrease in virus shedding, upregulation of IFN-α and IL-1β mRNA expression in the spleen, and type I IFN (IFN-α and IFN-β), IL-8, and IL-18 expression in the lungs [41].…”
Section: Toll-like Receptorsmentioning
confidence: 99%